Enhanced torque control in high-speed DTC using modified stator flux locus - Zawawi, Syed Abrar S. A.; Jidin, Auzani; Sabri, Nurul Syahada Muhamad; Tarusan, Siti Azura A.; Sutikno, Tole (International Journal of Power Electronics and Drive Systems (IJPEDS), 2025)
This paper proposes a modification of stator flux locus in direct torque control (DTC) of induction machine, aiming to enhance torque capability during steady-state operation at high speeds. The modified flux locus maintains the simplicity of the original DTC structure and its advantages of rapid torque and flux dynamic control. However, DTC faces challenges in controlling motor torque at high-speed operations. This study addresses the limitation of the traditional circular flux locus, which limits the angular frequency of stator flux to increase further and hence causes control of torque deteriorates at high speeds. By modifying the stator flux locus from a circular to a hexagonal shape by adjusting flux hysteresis band, this can improve torque control during high-speed motor operation. This finding has potential applications in industrial and electric vehicle sectors that demand enhanced torque control for high-speed motor operations.